Makna Setan dalam Antologi Cerpen “Arinillah” Karya Taufik Al-Hakim (Analisis Semiotik Carles Sanders Pirce) - Munawaroh; Susilawati, Ani (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2023)
The أرني الله anthology is the work of Taufik El-Hakim with the theme of philosophy. In the short story anthology, there are three short stories had been researched, namely, الشهيد , وكانت الدنيا, and المرأة غلبت الشيطان. The three short stories have similarities, such as the emergence of personage devil with with different characters, and the use of words and sentences have the shape of signs. Based on the uniqueness and the problem, the researcher reveals that the three short stories using Charles Sanders Pierc's Semiotic analysis knife. The method is descriptive qualitative method, the primary data source is the anthology of the short stories أرني الله by Taufik El-Hakim, and secondary data comes from books and other supporting articles. The research results are icons, indexes, and symbols which is found in the three short stories, such as the word